Size Selection And Monolayer Enrichement In Liquid Exfoliated Tungsten Disulphide Dispersions. - SZYDLOWSKA, BEATA MARIA (Trinity College Dublin. School of Physics. Discipline of Physics, 2018)
Since the the discovery of graphene in 2004, the scientific environment turned its great interest towards new type of nanomaterials, commonly called two dimensional (2D) layered nanomaterials. Over last 15 years, they consistently prove to have unique properties, which can only be seen when their lateral dimensions are taken into the nanoscale. Honouring their favourable properties, many new applications have emerged, rang- ing from gas sensing, transistor technologies, optical switches to energy storage devices. Although there are several methods to exfoliate layered crystals, Liquid Phase Exfoliation (LPE) method developed by Coleman et al. was used in work described in this thesis. It applies to a wide range of layered materials such as graphene, hexagonal boron nitride, transition metal dichalcogenides (including WS2) and even materials like talc or cat litter. This thesis is dedicated to in-depth investigation of Tungsten Disulphide (WS2), a semiconducting transition metal dichalcogenide (TMDC). De- scribed work starts with the WS2 powder and is aimed at the production of high-quality 2D nanosheets in aqueous dispersion (LPE). The size se- lected WS2 nanosheets dispersions are proven to be state of the art by a range of characterisation techniques. Those include AFM, TEM, Absorp- tion and Extinction Spectroscopy, Raman Spectroscopy and Photolumi- nescence spectroscopy. Moreover, the size dependent Nonlinear Optical (NLO) response of WS2 nanosheets are studied. Their saturable absorp- tion (SA), as well as optical limiting (OL) capabilities were demonstrated. Further, thanks to the development of multiple secondary cascades, WS2 dispersions are taken to an enriched level, where the monolayer volume fraction in the dispersions is ̃ 75%. Finally, high quality, uniform, op- tically active WS2-PMMA composite thin films are produced. They will surely find a real life application as the pristine properties of WS2 pro- duced from LPE are from now on accessible in the solid state.
APPROVED
Keywords: Transition Metal Dichalcegonides; 2D Nanomaterials; Liquid Phase Exfoliation; WS2; Z-scan; Size Selection; Photoluminescence